1994
DOI: 10.1063/1.111873
|View full text |Cite
|
Sign up to set email alerts
|

Degradation mechanisms and improvement of thermal stability of CoSi2/polycrystalline Si layers

Abstract: Degradation mechanisms of CoSi2/polycrystalline Si (polycide) films have been investigated. CoSi2 was formed on various silicon substrates (stacked or one-layer structures composed of polycrystalline Si 800–10 800 Å and amorphous Si 800–3000 Å). The thermal stability of these silicide films were examined using four-point probe measurement. It was found that the microstructure of the underlying silicon substrate, rather than the grain size of the CoSi2 or the silicide/polycrystalline Si interface, has the great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…This finding cohorts the claim that modifying the Si substrate is effective in tailoring layer inversion. 14 In this paper we have shown that the Ni͑Pt͒Si can be stabilized up to 800°C on RTCVD-Si and the stabilization was attributed to the preponderant role of the change in Gibbs free energy. Layer inversion was retarded due to the larger resultant poly-Si grains upon heat-treatment of the mixed phase films in the presence of Ni͑Pt͒.…”
mentioning
confidence: 81%
“…This finding cohorts the claim that modifying the Si substrate is effective in tailoring layer inversion. 14 In this paper we have shown that the Ni͑Pt͒Si can be stabilized up to 800°C on RTCVD-Si and the stabilization was attributed to the preponderant role of the change in Gibbs free energy. Layer inversion was retarded due to the larger resultant poly-Si grains upon heat-treatment of the mixed phase films in the presence of Ni͑Pt͒.…”
mentioning
confidence: 81%
“…A similar observation for the underlayer morphology was also made in a previous research. 14 The dopants implanted in the poly-Si layer have a great influence on thermal stability property. 15,16 …”
Section: Resultsmentioning
confidence: 99%
“…3 It is well known that thermal stability depends on many physical parameters and experimental conditions. 4 Moreover, the interface roughness plays a key role on the thermal stability of thin silicide films and on the electrical properties. 5,6 There are not many reports on the thermal evolution of interface roughness of CoSi 2 /Si͑001͒, though.…”
Section: Real-time X-ray Scattering Study On the Thermal Evolution Ofmentioning
confidence: 99%